Local Features of Tajiks’ Navruz Songs of Kashkadarya Oazis - Shernazarov, Akmal Andiyokulovich (International Journal of Psychosocial Rehabilitation, 2020)
In this article the myths and songs(folklore)about Navruz holiday are analyzed. As we know in Asian countries Navruz is considered to be one of the religious and national holidays widely celebrated by this people where they praise new day and the beginning of spring. Every and each region of Uzbekistan has its own folklore pieces to present this holiday celebration and devotions to nature blossoming. Various myths and legends are connected with this holiday in which people call it and find out similarities with new married bride. These myths have been studied by different scholars and folklorists for a long time. And pieces of their works are the topic of this article. Navruz is one of our most ancient holidays. It encompasses a number of ancient traditions that have survived from ancient times to the present day in connection with the celebration of the New Year. New Year, which is celebrated with the beginning of spring, the arrival of the New Year, the increase of warm days, the retreat of the cold, the awakening and rejuvenation of nature, the budding and flowering of the giant tree, is held with infinite luxury.